Comparison of Tubeless Mini Percutaneous Nephrolithotomy with Conventional Technique in a Tertiary Care Center - Gupta, Dipesh Kumar; Gnyawali, Arun; Jaiswal, Deepak (Journal of Nepalgunj Medical College, 2022)
Introduction: Mini Percutaneous Nephrolithotomy (mPCNL) is a safe and efficient method for management of nephrolithiasis. Post procedure nephrostomy tube drainage is considered as the standard practice. In recent years, tubeless mPCNL with the use of double J (DJ) stent alone has replaced the placement of the nephrostomy tube. Aims: This study intends to evaluate the safety and efficacy of tubeless Mini Percutaneous Nephrolithotomy. Methods: A total of 80 patients with Nephrolithiasis, admitted to Urology Unit of Nepalgunj Medical College, between September 2018 and September 2019 were enrolled in the study and divided into two groups: Tubeless group where tube was omitted and Standard Group where it was placed. The two groups were compared with respect to hemoglobin drop and blood transfusion requirement, hospital stay and analgesic requirement in the post-operative period. Results: Mean age of the patients was 34.30 ± 13.19 years. Mean stone size was 19.03 mm. The mean change in hemoglobin after standard mPCNL was 1.68 gm/dl and that in the tubeless group was 1.11 (p=0.018). The tubeless group had a significantly (p=0.001) shorter hospital stay (3.05 ± 1.23 days) compared to standard group (3.85 ± 0.86). The postoperative pain as assessed by visual analogue scale, was more in the standard group necessitating additional analgesia. It was significantly higher in the standard group at 12, 24, 48 hours, as compared to the tubeless group. Conclusion: Placement of nephrostomy tube can be omitted as a routine practice as Tubeless mini PCNL has an added advantage of significantly reduced postoperative pain, less analgesic requirement, shorter hospital stay, less postoperative blood loss.